De Swiet's medical disorders in obstetric practice - Powrie, Raymond O.; Greene, Michael F.; Camann, William; De Swiet, Michael (Wiley-Blackwell, 2010)
"Pregnancy affects the physiology of women as their bodies adapt to the growing life within them; but how does this affect how you manage general, or pre-existing medical complaints? How do you differentiate the effects of pregnancy from genuine medical conditions? What are the effects of the 'standard' treatments on the growing fetus? What about breastfeeding? In this brand-new edition of de Swiet's Medical Disorders in Clinical Practice, expert physicians present the best evidence and practical wisdom to guide you and your patients through their pregnancy and illness, to a successful birth and early motherhood. Using a combination of algorithms, years of experience and an evidence-based approach, this book will help you to: Diagnose difficult to identify conditions during pregnancy Effectively prescribe for pregnant and lactating women Overcome the challenges of imaging, anesthesia and critical care for pregnant women de Swiet's assists you in navigating the many challenges pregnancy presents for both the patient and physician."--Provided by publisher